A highly luminescent and stable copper halide ionic hybrid structure with an anionic CuBr2(tpp)2 module. Issue 37 (15th July 2021) - Tong, Hua; Xu, Chanchan; Liu, Wei
Abstract : A novel copper bromide ionic compound (bz-ted)CuBr2 (tpp)2 ·H2 O was reported. The inorganic module of the compound is CuBr2 − that has been coordinated to two tpp molecules, generating strong blue photoluminescence. Abstract : Here, we report a novel copper bromide ionic compound (bz-ted)CuBr2 (tpp)2 · H2 O (1, tpp = triphenylphosphine, and bz-ted = 1-benzyl-1, 4-diazabicyclo[2.2.2]octan-1-ium) by a facile wet chemistry method. The inorganic module of the compound is CuBr2 − coordinated to two tpp molecules, generating strong blue photoluminescence originating from the metal-to-ligand-charge-transfer (MLCT) process. The combination of both ionic bonds and covalent bonds in the hybrid cluster makes compound 1 strongly emissive, robust and solution-processable. Such a coordinated anionic inorganic module presents a new approach for the development of highly luminescent and stable copper halide ionic hybrid structures.